Antivirus endowed with Artificial Neural Network in order to Detect Malwares Preventively - Lima, Sidney Marlon Lopes de; Silva, Heverton Kleidson de Lima; Luz, João Henrique da Silva; Silva, Samuel Lopes de Paula; Lima, Hercília Juliana do Nascimento; Andrade, Anna Beatriz Augusta de; Silva, Alisson Marques da (iSys - Journal of Information Systems, 2018)
Malware is a software whose main goal is to access an device without the explicit permission of its owner. Antivirus is the most popular mechanism in order to detect malwares. Commercial antiviruses have as strategy to wait for a user to be infected and in sequence to report an anomalous behavior of her/his device, so that the antivirus manufacturer can take action. Then, in order to overcome the limitations of commercial antivirus, the proposed work creates an antivirus capable of preemptively identifying the modus operandi of a malicious application. The proposed antivirus employs artificial intelligence and can detect a malicious application even before it is run by the user. On average, the smart antivirus created can distinguish malware applications from benign ones in 98.13% of cases.